Effect of Graded Level of Alphamune G on Performance, Blood Chemistry and Histology of Cockerel Chicks - Bolu, S.A.; Ojo, V.; Oluyemi, O.; Babawale, O.I.; Awodele, O.A. (International Journal of Poultry Science, 2009)
A study was conducted to determine the response of day-old cockerel chicks to graded levels of Alphamune G (0.00, 0.04, 0.05 and 0.06%). The experiment which was conducted for 8 weeks employed a completely randomized design. Feed intake and nutrient retention were not significantly influenced (p>0.05) by dietary inclusion levels of Alphamune G. However, weight gain and feed to gain ratio were significantly improved (p